(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
It is known that studying the activities of farms specializing in the cultivation of fruits and vegetables, which occupy a significant place in the export of agricultural products in our country, and organizing it based on the introduction of innovations is of great importance in increasing the efficiency of these products. In this article, through a survey, the problems observed in the processes of growing, storing, processing and selling fruits and vegetables in farms and peasant households in the Kashkadarya region were studied, and appropriate proposals and recommendations were developed.